Nebulization Practice and use of Antibiotic in the Treatment of Childhood Asthma at the Rural Area - Alam, MD Shafiul; Yasmeen, B H Nazma; Md Benzamin, -; Haq, Nadia; Hasan, Md Shariful (Northern International Medical College Journal, 2021)
Background : Management of childhood asthma is not optimum in our country especially at the community level. Objectives : The study was conducted to see the nebulization practice in the management of moderate and sever acute asthma in children at the community level. Methodology : This cross-sectional observational study was conducted in different private clinics and pharmacy of Daudkandi Upazila of Cumilla during the period of November 2017 to March 2018. Total 30 doctors’ diagnosed cases of acute exacerbation of moderate and severe asthma between 2-15 years of age were included in this study. Each patient’s treatment advice was followed up to see whether the use of nebulized Salbutamol and Antibiotic in the management of acute asthma was appropriate or not. All data were recorded in to a pretested proforma. Data were analyzed manually, and values were expressed as frequency and percentage. Results : Among the cases 25 (83.33%) cases had moderate and 5 (16.67%) cases had severe exacerbation of asthma. For nebulization, salbutamol was used to all cases and ipratropium bromide was added to 11 (36.7%) cases. Nebulization frequency was as per national guideline but the ratio of salbutamol respiratory solution to normal saline was not appropriate in most of the cases. Antibiotic was given to all cases and among them parenteral Ceftriaxone was given to 22 (73.3%) cases. Conclusion : Frequency of nebulization was appropriate but ratio of Salbutamol respiratory solution to normal saline was inappropriate. Antibiotic was given to all cases. Northern International Medical College Journal Vol.11 (2) Jan 2020: 471-474